Association of miR-146aC>G, miR-149C>T, miR-196a2T>C, and miR-499A>G polymorphisms with risk of recurrent implantation failure in Korean women. (July 2016) - Cho, Sung Hwan; Chung, Ki Wha; Kim, Jung Oh; Jang, Hyogeun; Yoo, Jung Ki; Choi, Youngsok; Ko, Jung Jae; Kim, Ji Hyang; Nishi, Yoshihiro; Yanase, Toshihiko; Lee, Woo Sik; Kim, Nam Keun
Abstract: Objective: The aim of this study was to investigate the association of microRNA polymorphisms ( miR - 146a C> G, miR - 149 T> C, miR - 196a2 T> C, and miR - 499 A> G) in Korean patients with recurrent implantation failure (RIF). Methods: We conducted a case–control study of 354 Korean women: 120 patients with RIF and 234 healthy controls with at least one live birth and no history of pregnancy loss. Results: The combined miR-146aCG + GG / miR - 196a2CC genotype was more frequent in patients than in controls ( P < 0.05), and apparently conferred increased susceptibility. Conversely, genotype-based multifactor dimensionality reduction analysis, revealed that the G-T-T-A ( miR-146a/-149/-196a2/-499 ) and G-T-T inferred genotypes ( miR-146a/-149/-196a2 ) were significantly less frequent in patients, which suggested potential protective effects. The expression of miR-146a for the GG homozygote was significantly lower ( P < 0.05) than expression of the CC homozygote from both the pre, mature and sequences of miR-146a-3p ( P < 0.05 each). The expression of miR-196a2 for the CC homozygote was also lower than the TT homozygote from the mature sequence of miR-196a2-3p ( P < 0.05). Conclusions: These results suggest that the polymorphisms in miR-146a and miR-196a2 could alter their target mRNA expression. Our findings suggest that expression levels of miR - 146a C> G, miR - 196a2 T> C and putative gene–gene interaction between miR-146a, miR-196a2, miR-149 may be involved in RIF development in Korean women.